Implementasi Moderasi Beragama Dalam Membangun Kerukunan Umat Beragama - Windhi Wijaya; Sentot; Aryanto Firnadi (Jounal Nyanadassana, 2023)
The purpose of this research is to understand and describe the implementation of religious moderation in fostering interfaith harmony among religious communities. Religious moderation ensures that in practicing religious teachings, a follower should not be confined within limits that push towards extreme doctrines prioritizing one's own teachings, thus fostering mutual respect and honor amidst existing diversity. This research is qualitative in nature, employing a descriptive analytical approach. Data collection involves observation, interviews, and documentation. Data analysis comprises four stages: data condensation, data display, verification, and drawing conclusions. Primary and secondary data sources are used, obtained from interviews with village officials, religious figures, and community leaders. Other data sources include books, journals, theses, and relevant websites. The findings indicate that the implementation of religious moderation in building interfaith harmony is still lacking due to prevailing intolerance in religious practices. This intolerance manifests in forms such as violence, discrimination, extremism, fanaticism, and fundamentalism.